Colposcopic evaluation of unhealthy cervix and it’s correlation with Papanicolau smear in cervical cancer screening - Kalyankar, Vijay Y.; Kalyankar, Bhakti V.; Gadappa, Shriniwas N.; Kute, Supriya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: In present study colposcopic evaluation of unhealthy cervix was donr and it’s correlation with Papanicolau smear in screening of Cancer cervix. Objective of present study was to critically evaluate the sensitivity and specificity of PAP smear with that of Colposcopy in screening of Cancer Cervix in women with unhealthy cervix. Methods: 100 women with clinically unhealthy cervix on naked eye examination and / or abnormal symptoms attending Gynaecology Out patient department in 2 years period were subjected to PAP smear, Colposcopy, biopsies under Colposcopic guidance and findings correlated with Histopatholgy at Govt. Medical college, Aurangabad, Maharashtra. India. The sensitivity and specificity of PAP smear with that of Colposcopy in screening of Cancer Cervix was evaluated. Results: Both PAP smear and Colposcopy can be reliably used to screen women with premalignant lesions of Cancer cervix. Conclusions: Colposcopy is a better tool for diagnosis of precursors of Cancer Cervix than PAP Smear and Histopathology of suspected lesion remains the gold standard for final diagnosis.